Phatic emoji of javanese netizens in social media: a cyberpragmatics perspective on a creative communicative strategy - Widiana, Yuli; Syed Abdullah, Syed Nurulakla; Sumarlam, Sumarlam (Vilnius Gediminas Technical University Journals, 2024)
The massive shift of communication culture from direct to virtual channels due to the COVID-19 pandemic affected virtual politeness performance. The limitation of physical expression in digital platforms encourages emojis to replace gestures, mimics, and other expressions. This study aims to describe the types of speech acts and the function of the emojis along with the performance of politeness strategies in the WhatsApp group of Javanese netizens. Understanding politeness performance through the use of speech acts and emojis in virtual communication provides insights into how universal emojis are specifically used in a particular culture and shows the creativity of emoji use in phatic communication. The virtual textual data were taken from five WhatsApp group’s with 174 Javanese members by observation method. The emoji that occurred in the conversational texts were classified based on the types of speech acts and their functions. The analysis was conducted within the cyberpragmatics framework. The findings showed that emojis were used in assertive speech acts, directive speech acts, expressive speech acts, and phatic speech acts. The functions were to emphasize meaning, clarify meaning, direct certain actions, express feelings, and establish social rapport. The research contributes to the development of cyberpragmatics as the current approach in pragmatics study. Moreover, the findings depicted the current phenomenon of social media communication on a cultural basis.